Ventral striatum and amygdala activity as convergence sites for early adversity and conduct disorder - Holz, Nathalie E.; Boecker-Schlier, Regina; Buchmann, Arlette; Blomeyer, Dorothea; Jennen-Steinmetz, Christine; Baumeister, Sarah; Plichta, Michael M.; Schmidt, Martin H.; Meyer-Lindenberg, Andreas; Banaschewski, Tobias; Brandeis, Daniel; Laucht, Manfred (Social cognitive and affective neuroscience, 2017)
Abstract. Childhood family adversity (CFA) increases the risk for conduct disorder (CD) and has been associated with alterations in regions of affective proces
Advance access publication date: 30 September 2016
Gesehen am 27.08.2018